Synthesis, characterization and application of silver doped graphitic carbon nitride as photocatalyst towards visible light photocatalytic hydrogen evolution. (7th September 2020) - Paul, Devina Rattan; Sharma, Rishabh; Panchal, Priyanka; Nehra, S.P.; Gupta, A.P.; Sharma, Anshu
Abstract: In this study, the series of silver doped graphitic carbon nitride composites (GCN-Ag x ) were prepared by varying the amount of silver nitrate added in urea for thermal polymerisation reaction among the two precursors. The characterisation study of GCN-Ag x composites so obtained was performed using X-ray diffraction, fourier transform infrared spectroscopy, diffused reflectance spectra and Brunauer–Emmett–Teller analysis to explore the effect of silver doping on the various structural, morphological and optical aspects of pure graphitic carbon nitride (GCN-P). In addition, the GCN-Ag x composites were analysed for their photoactivity potential and it was found that silver doping can noticeably enhance the photoactivity potential of GCN-P. The phenomenon of enhanced photoactivity was ascribed to the synergistic effect of silver nanoparticles and GCN-P resulting in the increased ability towards visible light absorption, delayed recombination and better separation of photogenerated charge carriers. The synthesized catalyst could be considered as a potential photocatalyst for environmental and energy applications. Graphical abstract: Image 1 Highlights: GCN-Ag x composites were prepared using silver nitrate and urea. GCN-Ag x composites were analysed for photocatalytic activity towards methylene blue degradation. Synergistic effect among silver nanoparticles and GCN-P leads to enhanced photocatalytic activity. Temporary charge trapping site due to incorporated Ag nanoparticles played a vital role in photocatalysis.